Comparing therapeutic effects of hematopoietic stem cell transplantation, tyrosine kinase inhibitors and chemotherapy in adult patients with Philadelphia chromosome-positive acute lymphoblastic leukemia: a systematic review and meta-analysis - Gao, Xiaohui; Zeng, Hui; Sun, Fei; Zhao, Xiaoyan; Wu, Haibing; Yan, Minchao; Li, Yuan; Fu, Qinyan; Zhang, Gang (Frontiers in Oncology, 2025)
ObjectiveBoth hematopoietic stem cell transplantation (HSCT) and chemotherapy combined with tyrosine kinase inhibitors (TKIs) have shown therapeutic efficacy in patients with Philadelphia chromosome-positive (Ph+) acute lymphoblastic leukemia (ALL). This study aimed to compare the clinical outcomes of HSCT and TKI-combined chemotherapy regimens in Ph+ ALL through a meta-analysis.MethodsWe systematically searched PubMed (from 1966), Embase (from 1974), and the Cochrane Library (from 1993) up to April 30, 2025, for eligible studies. Overall survival (OS) and disease-free survival (DFS) were evaluated using hazard ratios (HRs) with 95% confidence intervals (CIs), while relapse risk was assessed using odds ratios (ORs) with 95%CIs. A random-effects model was applied for all analyses.ResultsThe meta-analysis included 35 studies involving 3,827 patients with Ph+ ALL. Allogeneic HSCT (allo-HSCT) was associated with significantly better OS (HR: 0.60; 95% CI: 0.45–0.81; P = 0.001) and DFS (HR: 0.40; 95% CI: 0.30–0.54; P < 0.001) compared to TKI-based chemotherapy. No significant differences in OS (HR: 0.97; 95% CI: 0.70–1.34; P = 0.845) or DFS (HR: 0.92; 95% CI: 0.67–1.26; P = 0.605) were observed between allo-HSCT and autologous HSCT (auto-HSCT). Moreover, allo-HSCT was associated with a significantly lower relapse risk than both TKI-based chemotherapy (OR: 0.28; 95% CI: 0.16–0.51; P < 0.001) and auto-HSCT (OR: 0.39; 95% CI: 0.27–0.54; P < 0.001).ConclusionThis meta-analysis demonstrates that allo-HSCT provides superior survival outcomes compared to TKI-based chemotherapy in patients with Ph+ ALL. Although survival outcomes are similar between allo-HSCT and auto-HSCT, allo-HSCT is associated with a significantly reduced risk of relapse.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier INPLASY202550012.